Chapter 15: Decolonial critique in AI policy-making and policy analysis - Gray, Catriona (Edward Elgar Publishing, 2024)
This chapter examines how decolonial thinking and practice can support a critical research agenda on AI technologies and public policy. Decolonial critique offers a key framework for uncovering the power relations that shape the design, development, and use of AI technologies. The chapter first introduces decolonial critique and demonstrates how it has been applied by various thinkers to make sense of the origins, practices, and effects of AI. Colonialism, as this literature suggests, shapes both AI’s conditions of possibility, and the conditions under which AI technologies are produced today. The chapter then demonstrates two further advances that a decolonial critique makes available: (1) a multiplication of the lenses we use to understand and recognise AI harms, and (2) a more critical account of the role of the state.